RANCANG BANGUN SISTEM INFORMASI PENJUALAN STIKER BERBASIS WEBSITE - Andika Ilham Pradana; Rava Eka Cahyono; Restu Narendrastomo; Dewi Oktafiani (Jurnal Riset Multidisiplin Edukasi, 2026)
This research aims to create a web-based sticker sales information system to facilitate a more organized and efficient sales process. The system development method used is the Waterfall method, which consists of requirements analysis, system design, system development, testing, and maintenance. The system was built using the PHP programming language with the assistance of HTML5, CSS3, and Bootstrap 5 for the display, and MySQL as the database. The results of the research indicate that the system can effectively implement key features such as user login, product data management, shopping cart, checkout, invoice creation, and admin order management. Testing results indicate that the system operates as designed and facilitates online sales transactions for users. Therefore, this web-based sales information system can be a solution to increase the effectiveness and efficiency of the sales process compared to manual methods.